Cognitive and motor disturbances in depression: insights from comprehensive behavioral assessments - Douka, Ioanna; Ruitenberg, Marit F. L.; Weischedel, Kamile; Phouthavongsay, Carlos; Weisenbach, Sara L.; van der Geest, Jos N.; Mickey, Brian J.; Koppelmans, Vincent (Frontiers in Psychiatry, 2025)
BackgroundDepression affects not only mood and reward processing, but also motor and cognitive functioning, leading to psychomotor disturbances crucial for diagnosis, prognosis, and treatment. Patients with severe psychomotor retardation often respond poorly to SSRIs but benefit from neurostimulation like ECT. However, comprehensive assessments of cognitive and motor domains in the same depression sample are rare.MethodsThis pilot study compared 20 depressed patients and 22 controls across multiple tests of cognitive and motor functions. We examined executive function and processing speed (Symbol Digit Modalities Test (SDMT), D-KEFS Color-Word Interference Test), verbal and visual learning and memory (Hopkins Verbal Learning Test (HVLT-R), and Brief Visuospatial Test (BVMT-R), gait (2-minute walking, 4-meter walking and walking while talking (WWT) tests), sarcopenia (grip strength ftest, knee extension test), and fine motor function (Archimedes Spiral Test, 9 Hole Peg Test). Associations between depression severity and behavioral performance were also explored.ResultsDepressed participants performed significantly worse on the color naming and interference conditions within the D-KEFS Color-Word Interference Test and on the HVLT's delayed recall. They were slower on the 9 Hole Peg Test with both their dominant and nondominant hands, while no differences were noted in gait or sarcopenia. Greater depression severity correlated with poorer performance on the WWT dual cognitive-motor task and quicker movement on the Archimedes Spiral task.ConclusionsThese findings reveal decrements in cognitive and motor domains in depressed individuals, which could impact daily functioning. Overall, results from this pilot study suggest that examining motor disturbances alongside cognitive disturbances could serve as a marker of disease progression and a potential target for intervention.